"Behind bars: understanding prisoner perception of penitentiary rehabilitation in Kazakhstan" - Mukasheva, Dalida (International journal of law, crime and justice, 2024)
This study focuses on identifying factors that, from the perspective of prisoners, contribute to positive perceptions of rehabilitation (correction) in prison. A survey was conducted of 645 soon-to-be-released inmates (530 males and 115 females) in five institutions, with questions covering demographics, incarceration details, access to social services, and personal values. The research revealed that male inmates tended to hold more positive views on penitentiary rehabilitation than female inmates. However, it was observed that the rigidity of the prison regime and the existence of chronic illnesses among inmates negatively influenced these positive perceptions towards rehabilitation. Furthermore, the implementation of diverse rehabilitation-focused initiatives by non-governmental organisations (NGOs), coupled with an awareness of rights and responsibilities and the presence of strong family values, has been linked to fostering positive perceptions of rehabilitation. These findings highlight the critical need for enhanced cooperation between non-governmental organisations and prison facilities, as well as the introduction of social work practices within Kazakhstan's prison system. Policymakers should consider these factors when designing evidence-based rehabilitation strategies, emphasising the utilization of social work technologies.